Mechanical properties and fracture toughness of polypropylene reinforced kenaf fibre and nanoclay composites / Nur Kamarliah Kamardin - Kamardin, Nur Kamarliah (2017)
This research was carried out to study the effects of kenaf fiber (K) and nanoclay (NC) loadings on the mechanical properties and fracture toughness of polypropylene (PP) reinforced kenaf fiber and nanoclay composites. There were three composite system involve in this study, namely polypropylene/nanoclay (PP/NC), kenaf/polypropylene (KPP) and kenaf/polypropylene/nanoclay (KPP/NC) composites. Kenaf fibre (160 - 250 µm) loadings were varied at 20 wt%, 30 wt% and 40 wt%, meanwhile nanoclay loadings were varied at 0, 3 and 6 phr (part per hundred resin). Thermal mixer was used to mix kenaf, polypropelene and nanoclay to produce composite pellets and the pellets were injection molded to produce composite test specimens. The tensile test, impact test and fracture test were performed according to ASTM D638, ASTM D256 and ASTM D5045 respectively. Incorporation of 6 phr NC to the PP had resulted in a decreased about 8% in tensile strength and 44% in impact strength, however its fracture toughness had increased about 58%. The incorporation of kenaf fiber had lowered 19% of the tensile strength compared to pure PP. The impact strength decreased meanwhile the fracture toughness had indicated an increment about 14% as the kenaf loading increased. PP with 6 phr nanoclay was the highest tensile strength with 22.48 MPa. PP with 3 phr nanoclay composite showed the highest impact strength with the value of 12 kJ/m2 whilst 40% of kenaf loading with 6 phr nanoclay was the highest fracture toughness of about 2.02 MPa.m1/2.